Cracking Behaviors and Mechanical Properties of Rock-Like Specimens with Two Unparallel Flaws under Conventional Triaxial Compression. (1st April 2019) - Le, Huilin; Sun, Shaorui; Xu, Chenghua; Li, Liuyang; Liu, Yong
Abstract : Flaws existing in rock masses are generally unparallel and under three-dimensional stress; however, the mechanical and cracking behaviors of the specimens with two unparallel flaws under triaxial compression have been rarely studied. Therefore, this study conducted comprehensive research on the cracking and coalescence behavior and mechanical properties of specimens with two unparallel flaws under triaxial compression. Triaxial compressive tests were conducted under different confining pressures on rock-like specimens with two preexisting flaws but varying flaw geometries (with respect to the inclination angle of the two unparallel flaws, rock bridge length, and rock bridge inclination angle). Six crack types and eleven coalescence types in the bridge region were observed, and three types of failure modes (tensile failure, shear failure, and tensile-shear failure) were observed in experiments. Test results show that bridge length and bridge inclination angle have an effect on the coalescence pattern, but the influence of bridge inclination angle is larger than that of the bridge length. When the confining pressure is low, coalescence patterns and failure modes of the specimens are greatly affected by flaw geometry, but when confining pressure rose to a certain level, the influence of confining pressure is larger than the effect of flaw geometry. The peak strength of the specimens is affected by flaw geometry and confining pressure. There is a critical value for the bridge length. If the bridge length is larger than the critical value, peak strengths of the samples almost keep constant as the bridge length increases. In addition, as the bridge inclination angle increases, there is an increase in the probability of tensile cracks occurring, and with an increase in the confining pressure, the probability of the occurrence of shear cracks increases.